The importance of considering small-scale variability in macrobenthic distribution: spatial segregation between two fiddler crab species (genus Leptuca) (Decapoda, Ocypodidae) - Checon, Helio H.; Costa, Tânia M. (Museu de Ciências Naturais, 2018)
ABSTRACT Defining the appropriate scale is important when trying to understand distribution patterns in community studies. Fiddler crabs are among the most common organisms inhabiting estuarine environments, and despite having a wide latitudinal distribution, are limited by shifts in temperature, current and wind pattern. Thus, many co-occur at a local scale, where their distribution is influenced by variables such as mean sediment grain diameter, salinity and tidal level. Our goal was to test intra and interspecific segregation in two similar and commonly co-occurring fiddler crabs species (Leptuca leptodactyla and Leptuca uruguayensis) at a small scale (10 m²). Interspecific segregation was observed, with L. leptodactyla occurring mainly at the upper level in relation to the water line and L. uruguayensis, at the lower. However, this pattern was irrespective of sex and developmental stage, as no intraspecific segregation was seen. Possible impacts of tidal level, soil silt/clay content and competition on interspecific segregation are discussed. Although L. leptodactyla and L. uruguayensis overlap in their occurrence when intertidal zonation is disregarded, they segregate when tidal levels are individually sampled as habitats. This highlights the importance of small-scale studies to identify patterns unobserved at regional scales, even when no environmental gradient is readily apparent.

RESUMO Definir a escala apropriada de um estudo é importante quando tentamos entender os padrões de distribuição em estudos de comunidade. Caranguejos chama-maré estão entre os organismos mais comuns que habitam os ambientes estuarinos, e apesar de possuírem uma ampla distribuição latitudinal, são limitados por alterações em temperatura, correntes e padrões dos ventos. Dessa forma, muitas espécies co-ocorrem em escala local, onde suas distribuições são influenciadas por variáveis como diâmetro do grão de sedimento, salinidade e nível de maré. Nosso objetivo foi testar a segregação intra- e interespecífica em duas espécies similares de caranguejos chama-maré, que comumente são encontradas em co-ocorrência (Leptuca leptodactyla e Leptuca uruguayensis), em uma pequena escala (10 m²). Foi observada segregação interespecífica, com L. leptodactyla ocorrendo primariamente no nível superior em relação à linha de maré, e L. uruguayensis no inferior. Entretanto, esse padrão foi independente de gênero e estágio de desenvolvimento, uma vez que segregações intraespecíficas não foram registradas. Possíveis influências do nível de maré, teor de silte/argila e competição na segregação interespecífica são discutidas. Apesar de L. leptodactyla e L. uruguayensis terem sobreposição em ocorrência quando a zonação do entremarés é desconsiderada, elas segregam quando os níveis de maré são individualmente amostrados. Esse resultado destaca a importância de estudos em pequena escala para identificar padrões não observados em escala regional, mesmo quando nenhum gradiente ambiental é inicialmente observado.
A importância de considerar a variabilidade em pequena escala na distribuição macrobêntica: segregação espacial entre duas espécies de caranguejo chama-maré (gênero Leptuca) (Decapoda, Ocypodidae)
Keywords: Fiddler crabs; estuarine beach; small-scale; Leptuca; allometric growth; Caranguejos chama-maré; praia estuarina; pequena escala; Leptuca; crescimento alométrico